Implementation of Huffman Code Algorithm for Message Compression and Decompression - Serdano, Akbar; Azzahra, Chairunnisa; Alpamah, Darus; Batubara, Ilham Fajar; Qasthari, Mohd. Wildan (Journal of Computer Science and Informatics Engineering, 2024)
Advances in information technology have brought significant changes in the way we transmit data. Data compression is a long-developed method that allows us to reduce the size of a file or message without losing important data in the file. By using the Huffman Code algorithm the size of the message in compression can save or reduce the size by approximately 70%. Huffman is a lossless compression algorithm, so when decompressed it will produce data that is identical to the original data before compression. The Huffman Code algorithm is implemented into the program to test the data used. The data used for this research comes from short message text.